Self-action of a Gaussian beam in a nematic liquid crystal cell - Reshetnyak, V.; Subota, S. (Condensed Matter Physics, 2001)
We present a theoretical study of the possibility of optical singularity birth in a wave front of a laser beam passing through a homeotropically aligned nematic liquid crystal (LC) cell. At intensities below some threshold value there is no any distortion in the initial homogeneous homeotropic LC alignment. When light intensity becomes higher than this threshold value, LC director deviates from its initial orientation. Strong director anchoring at the cell walls is assumed. Inhomogeneous director profile leads to the modulation of refractive index which in its turn may be considered as a Gaussian lens formed in the LC cell. This lens gives birth to the phase singularities in coherent beam with initially smooth wave front. At small values of director deviation in geometrical optics approximation one can find the light field just after the LC cell, and utilizing the Huygens-Fresnel principle calculate spatial position of the phase singularity at near field as a function of intensity of the input beam.